2017
DOI: 10.1016/j.cub.2017.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Direct Brain Stimulation Modulates Encoding States and Memory Performance in Humans

Abstract: People often forget information because they fail to effectively encode it. Here, we test the hypothesis that targeted electrical stimulation can modulate neural encoding states and subsequent memory outcomes. Using recordings from neurosurgical epilepsy patients with intracranially implanted electrodes, we trained multivariate classifiers to discriminate spectral activity during learning that predicted remembering from forgetting, then decoded neural activity in later sessions in which we applied stimulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
226
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 236 publications
(258 citation statements)
references
References 52 publications
11
226
1
Order By: Relevance
“…Improvement in verbal memory was demonstrated with chronic hippocampal stimulation delivered in response to seizures and epileptiform activities using a responsive neurostimulation device (RNS) [7]. Studies with acute hippocampal stimulation have shown positive and negative effects on memory depending on stimulation frequencies (1–50 Hz versus > 100 Hz) and site of stimulation (hippocampal versus fornix stimulation) [8], [9], [10], [11]. Note that the stimulation in these studies did not induce a seizure, unlike our study.…”
Section: Discussioncontrasting
confidence: 50%
“…Improvement in verbal memory was demonstrated with chronic hippocampal stimulation delivered in response to seizures and epileptiform activities using a responsive neurostimulation device (RNS) [7]. Studies with acute hippocampal stimulation have shown positive and negative effects on memory depending on stimulation frequencies (1–50 Hz versus > 100 Hz) and site of stimulation (hippocampal versus fornix stimulation) [8], [9], [10], [11]. Note that the stimulation in these studies did not induce a seizure, unlike our study.…”
Section: Discussioncontrasting
confidence: 50%
“…Attempts to enhance memory through invasive and noninvasive modulation of neural activity (for a review, see Kim et al, 2016) may prove more efficacious by accounting for the state of the brain when stimulation is applied. Recent work has demonstrated that the ability to enhance memory performance via direct brain stimulation during encoding is dependent upon the state of the brain (Ezzyat et al, in press). Given the correspondence between electrophysiological states and proper memory function, our findings suggest that perturbation of this network during retrieval, in addition to encoding, is likely to modulate memory function.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that altering neural networks in a way that either terminates seizures as soon as they are detected (eg, RNS), or pushes epileptic networks to self‐organize into a different dynamic pattern that is less likely to generate seizures, is a viable path forward to new therapies. Consistent with the arguments for seizures, direct modification of neural circuits could also positively affect the comorbidities, given that these are also emergent behaviors of an abnormally behaving complex system …”
Section: A Network Level Definition Of Mechanismsmentioning
confidence: 71%
“…Consistent with the arguments for seizures, direct modification of neural circuits could also positively affect the comorbidities, given that these are also emergent behaviors of an abnormally behaving complex system. [38][39][40] The emphasis of treatment has been on the prevention of seizures. However, conceptualizing epilepsy in a complex systems framework opens the door to treatments that directly target comorbidities.…”
Section: Definition Of Mechanismsmentioning
confidence: 99%